2021
DOI: 10.3389/fpubh.2021.603331
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Mental Health Among Chinese Medical and Non-medical Students in the Early Stage of the COVID-19 Pandemic

Abstract: Background: The 2019 coronavirus disease (COVID-19) pandemic is a public health emergency of international concern. This study aimed to assess the psychological outcomes and their influencing factors among medical and non-medical University students during the COVID-19 pandemic in China.Methods: A cross-sectional online survey using structured questionnaires was conducted from February 20 to March 20, 2020. Psychological outcomes were assessed according to the Depression, Anxiety, and Stress Scale (DASS-21). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 36 publications
10
38
1
Order By: Relevance
“…This was not consistent with a previous study by Ma, Z. et al (2020), in which it was found that freshmen tended to have less academic pressure and worry less about the future [ 43 ]. Consistent with another study by Xiong P. et al (2020), we found that students of non-medical colleges reported a higher prevalence of mental distress than medical students [ 44 ], and a higher level of distress was found among those who reported a history of chronic diseases, and, according to Louvardi, M. et al (2020) [ 45 ], a higher level of mental distress was experienced by low-income students (500 JD and below) and high-income students (1500 JD and above). Previous studies showed that levels of stress decrease with age as the older population has a lower level of knowledge about possible complications of disease, and they have greater faith and submission to mortality [ 46 ], which could explain why younger students, first year students and single students had a higher level of mental distress compared to others.…”
Section: Discussionsupporting
confidence: 92%
“…This was not consistent with a previous study by Ma, Z. et al (2020), in which it was found that freshmen tended to have less academic pressure and worry less about the future [ 43 ]. Consistent with another study by Xiong P. et al (2020), we found that students of non-medical colleges reported a higher prevalence of mental distress than medical students [ 44 ], and a higher level of distress was found among those who reported a history of chronic diseases, and, according to Louvardi, M. et al (2020) [ 45 ], a higher level of mental distress was experienced by low-income students (500 JD and below) and high-income students (1500 JD and above). Previous studies showed that levels of stress decrease with age as the older population has a lower level of knowledge about possible complications of disease, and they have greater faith and submission to mortality [ 46 ], which could explain why younger students, first year students and single students had a higher level of mental distress compared to others.…”
Section: Discussionsupporting
confidence: 92%
“…By summarizing the results presented above, we obtain three major findings. Firstly, we have found that in the face of a serious unknown public health emergency such as the COVID-19 pandemic, personal health is a concern of the highest priority in the early stages, which is consistent with the results of the survey by Xiong et al ( 40 ) and Apuke and Omar ( 41 ). Our study further supports this assertion in terms of the distribution of rumor topics and the dynamic of the psychosocial characteristics.…”
Section: Discussion and Implicationsupporting
confidence: 89%
“…However, the regularity of these widely circulated rumors changing in topic over time and the implied psychosocial characteristics of the public have not received sufficient attention. After earlier opinion-based or commentary explorations ( 41 ), some studies have tried to find the behavioral intention of the public to disseminate information during the pandemic as well as antecedents through questionnaires or laboratory experiments ( 17 , 40 ). However, such cross-sectional and self-reported data sources not only lack objectivity, but also the generality of the results is limited by the sample and, in addition, cannot give a concrete and dynamic understanding of the psychological changes of the public.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Depression, anxiety, and stress defined as score of ≥ 10, ≥ 8, and ≥ 15, respectively. The scale has good reliability and validity and can be used as an effective tool for investigating the mental health of Chinese college students (the Cronbach’s α was 0.81, 0.80, and 0.87 for the depression, anxiety, and stress subscale, respectively) ( Xiong et al, 2021 ). In this study, the Cronbach’s α reliability coefficients for each subscale were also good (depression α = 0.900, anxiety α = 0.868, and stress α = 0.874) and the test–retest reliability was 0.971.…”
Section: Methodsmentioning
confidence: 99%